2017
DOI: 10.13080/z-a.2017.104.036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substrates on yield and quality of strawberry fruits cultivated in a heated foil tunnel

Abstract: The experiment was aimed at comparing the effects of two types of peat-coconut substrates used for strawberry (Fragaria ananassa Duch.) cultivation in the soilless system. The study results demonstrated a direct effect of the substrate on the yield quantity and quality of strawberry fruits. Cultivar 'Albion' proved to have the highest yield under conditions of hydroponic cultivation. A higher yield as well as increased contents of extract, sugars, organic acids, polyphenols, and anthocyanins were found in frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…The highest TSS content in the strawberries was 10.2% (Table 9). It was lower than the values noted in the experiments conducted by Wysocki et al [50] (13.23%) and Mikiciuk et al [45] (12.37%). The application of humic acids had a positive effect on the content of the extract in strawberries.…”
Section: Treatmentscontrasting
confidence: 62%
“…The highest TSS content in the strawberries was 10.2% (Table 9). It was lower than the values noted in the experiments conducted by Wysocki et al [50] (13.23%) and Mikiciuk et al [45] (12.37%). The application of humic acids had a positive effect on the content of the extract in strawberries.…”
Section: Treatmentscontrasting
confidence: 62%
“…Meanwhile, anthocyanin content significantly increased in fruits grown in the net house with cocopeat treated soil (30.80 mg 100 g -1 ). Increased content of anthocyanins was observed in fruits from plants grown on the peat-coconut substrate (Wysocki et al, 2017). This study showed the positive influence of shade on the total anthocyanin content of the strawberry.…”
Section: Effect Of Different Shade Houses and Growing Media On Fruit ...supporting
confidence: 51%
“…It is clear that the cultivation substrate has a significant impact on both the appearance and the intrinsic quality of the fruit. The analyses of Wysocki et al also indicated that the cultivation substrate has a direct impact on the quality of the fruit, and a peat-coconut (50:50, v / v ) substrate yielded higher sugar, acid, polyphenol, and anthocyanin contents of strawberry fruit [ 36 ].…”
Section: Discussionmentioning
confidence: 99%